Role of metal ions in the cognitive decline of Down syndrome - Malakooti, Nakisa; Pritchard, Melanie A.; Adlard, Paul A.; Finkelstein, David I. (Frontiers in Aging Neuroscience, 2014)
Down syndrome (DS), caused by trisomy of whole or part of chromosome 21 is the most common mental impairment. All Down syndrome (DS) individuals suffer from cognitive decline and develop Alzheimer’s disease (AD) by the age of forty. The appearance of enlarged early endosomes, followed by Amyloid β peptide deposition, the appearance of tau-containing neurofibrillary tangles and basal forebrain cholinergic neuron (BFCN) degeneration are the neuropathological characteristics of this disease. In this review we will examine the role of metal ion dyshomeostasis and the genes which may be involved in these processes, and relate these back to the manifestation of age-dependant cognitive decline in DS.